2017
DOI: 10.4103/jisp.jisp_125_17
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic peripheral ossifying fibroma in a young adolescent girl: A very rare clinical presentation

Abstract: The use of the term “fibroma” for any soft-tissue lesion or gingival lesion by general practitioners has led to inadequate diagnosis of quite a few rare entities. The occurrence of gingival lesions in adolescent female patients is a routine clinical finding. The site of occurrence of such a lesion is of prime significance, as the rarity of these lesions is determined by the site and size of the lesion. On the other hand, the dilemma over the diagnosis of peripheral ossifying fibroma (POF) versus peripheral odo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Yu [11] reported a case, very similar to the one reported by Lima et al, of a diffuse POF in a 13 years old girl, localized on the maxilla, mandible, and palate, presenting with difficulties in speech, feeding, and oral hygiene; after a first debulking, the patient received a more aggressive excision in the following year that allowed complete healing without recurrence. Hasanuddin [29] reported a maxillary POF in a 15 years old female that impeded lip competence because of its dimension of 2.4 x 2 cm, without radiolucency on the orthopantomography; the patient was subjected to an excisional biopsy with a scalpel following a bone debridement, and no recurrence was detected after 2 years. Nair and Tewari [30,31] described two similar cases of POF located in the anterior mandible, respectively in 3 and 2 months patients, with medical history of neonatal teeth; in both cases, lesions did not allow correct breastfeeding, so their surgical excision was necessary.…”
Section: Pof In Pediatric Patients: Analysis Of the Recent Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Yu [11] reported a case, very similar to the one reported by Lima et al, of a diffuse POF in a 13 years old girl, localized on the maxilla, mandible, and palate, presenting with difficulties in speech, feeding, and oral hygiene; after a first debulking, the patient received a more aggressive excision in the following year that allowed complete healing without recurrence. Hasanuddin [29] reported a maxillary POF in a 15 years old female that impeded lip competence because of its dimension of 2.4 x 2 cm, without radiolucency on the orthopantomography; the patient was subjected to an excisional biopsy with a scalpel following a bone debridement, and no recurrence was detected after 2 years. Nair and Tewari [30,31] described two similar cases of POF located in the anterior mandible, respectively in 3 and 2 months patients, with medical history of neonatal teeth; in both cases, lesions did not allow correct breastfeeding, so their surgical excision was necessary.…”
Section: Pof In Pediatric Patients: Analysis Of the Recent Literaturementioning
confidence: 99%
“…The most reported and performed surgery consists of scalpel, followed by bone debridement, tooth scaling and root planning, with an approach that is as conservative as possible [39]. Of the 12 studies conducted on pediatric patients that we considered in this review, 9 authors have preferred this conventional treatment strategy because of its wellestablished reliability [8,11,14,20,25,26,28,29,32]. The remaining 3 authors reported the surgical excision of POF in newborns using diode laser [27,30,31].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…It usually arises from the cells in the periodontal ligaments and periosteum; mainly the interdental part of the anterior mandibular teeth. Moreover, the prevalence of POF is high among teenager and young adult females [ 1 ].…”
Section: Introductionmentioning
confidence: 99%